A note on strandings of Bryde's whales (Balaenoptera edeni) in the southwestern Atlantic - Lima, Eduardo Cabral Casado (J. Cetacean Res. Manage., 2020)
The aim of the present study is to trace a diagnosis of Bryde´s whale (Balaenoptera edeni) strandings in jurisdictional Brazilian waters through the compilation of published records and those conveyed in communication channels. During 1972 and 2015, 74 strandings were documented between the states of Rio Grande do Sul and Rio de Janeiro, Bahia and Maranhão. The results point out statistically significant differences between the frequencies of strandings in relation to Brazilian regions (χ² = 103.17), with the highest abundance found for the Southeast region (71.62%). Statistically significant differences were also observed between stranding frequency and sexual maturity (χ² = 12.31), with a higher abundance for sexually mature females(54.25%). No statistically significant difference between the stranding frequency in relation to seasonality (χ² = 2.34) was observed. Regarding sex, no statistically significant difference between stranding frequency for males and females was found (χ²=3.12). A trend of increasing B.edeni strandings was observed from the 1980s onwards, by the use of a simple linear regression. This may be due to population growth of the species, increased monitoring throughout the Brazilian coast, and/or increased anthropogenic threats. Thus,stranding monitoring is important for the adoption of conservation measures for this species, as well as for the determination of regional stocks through genetic analyses.